Parametric Optimization and Process Performance Analysis During WEDM of P91 Steel - Yadav L.K.; Kumar V.; Siddiqui S.; Misra J.P.; Upadhyay V. (My University, 2025)
P91 steel is a typical heat-resistant material widely used in power plant and petrochemical industries. It is challenging to machine P91 steel using conventional methods. Hence wire electrical discharge machining (WEDM) is employed in this study to machine P91 steel. The objective of this study is to construct a reliable WEDM process utilizing the design of experiments (DOE) experimental approach. In accordance with the experimental design, the parameters pulse on time, pulse off time, wire speed, and peak current are changed to determine their impacts on cutting speed, surface roughness, and material removal rate (MRR). Further, an effort has been made to model these three response variables using the response surface methodology (RSM). To evaluate the importance of machining process parameters, analysis of variance (ANOVA) is employed. The created RSM model is supported and validated by the test results. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.